Association of Kidney Function With Major Postoperative Events After Noncardiac Ambulatory Surgeries: A Population-Based Cohort Study. Issue 2 (10th February 2023) - Harrison, Tyrone G.; Hemmelgarn, Brenda R.; James, Matthew T.; Manns, Braden J.; Tonelli, Marcello; Brindle, Mary E.; McCaughey, Deirdre; Ruzycki, Shannon M.; Zarnke, Kelly B.; Wick, James; Ronksley, Paul E.
Abstract : Objective: The aim of this study was to estimate the association between estimated glomerular filtration rate (eGFR) and acute myocardial infarction (AMI) or death after ambulatory noncardiac surgery. Summary Background Data: People with chronic kidney disease (CKD) commonly undergo surgical procedures. Although most are performed in an ambulatory setting, the risk of major perioperative outcomes after ambulatory surgery for people with CKD is unknown. Methods: In this retrospective population-based cohort study using administrative health data from Alberta, Canada, we included adults with measured preoperative kidney function undergoing ambulatory noncardiac surgery between April 1, 2005 and February 28, 2017. Participants were categorized into 6 eGFR categories (in mL/min/1.73m 2 )of ≥60 (G1–2), 45 to 59 (G3a), 30 to 44 (G3b), 15 to 29 (G4), <15 not receiving dialysis (G5ND), and those receiving chronic dialysis (G5D). The odds of AMI or death within 30 days of surgery were estimated using multivariable generalized estimating equation models. Results: We identified 543, 160 procedures in 323, 521 people with a median age of 66 years (IQR 56–76); 52% were female. Overall, 2338 people (0.7%) died or had an AMI within 30 days of surgery. Compared with the G1–2 category, the adjusted odds ratio of death or AMI increased from 1.1 (95% confidence interval: 1.0–1.3) for G3a to 3.1 (2.6–3.6) for G5D. Emergency Department and Urgent Care Center visits within 30 days were frequent (17%), though similar across eGFR categories. Conclusions: Ambulatory surgery was associated with a low risk of major postoperative events. This risk was higher for people with CKD, which may inform their perioperative shared decision-making and management.